The Effect of Compensation and Leadership Style on Employee’s Working Performance with Job Satisfaction as a Moderating Variable (Case Study at CV Royal ATK Malang) - Anis Dwiastanti; Affan Aldi Nafian (Jurnal Ilmu Manajemen Advantage, 2022)
A human resource is a vital resource for the organization. The strength and weakness of the organization will be effected by the management of human resource as the driving force of the organization. Therefore, compensation and leadership factors are elements that can affect employee satisfaction and performance. This study aims to examine the effect of compensation and leadership style on employee satisfaction and performance at CV Royal ATK Malang. This study used an explanatory research approach, using a questionnaire as a data search tool. All 100 employees of CV Royal ATK were used as saturated samples in this study. Data analysis techniques use Path Analysis. The results of the study show that compensation and leadership style have an influence on job satisfaction. Compensation and leadership style also have an influence on performance. Job satisfaction has a significant effect on employee performance at CV Royal ATK Malang. The research results also note that job satisfaction is proven to be able to mediate the relationship between compensation and performance and job satisfaction is able to mediate the relationship between leadership and employee performance.